Digitally-enhanced medication-assisted treatment for opioid use disorder: acceptability, engagement and treatment retention - Palacios, Jorge E.; Sherrick, Robert; Lorenzen, Sara; Tregarthen, Jenna (Frontiers in Psychiatry, 2025)
BackgroundOpioid use disorder (OUD) is a persistent public health crisis, with medication for opioid use disorder (MOUD) significantly reducing overdose risk and improving outcomes. However, treatment adherence and retention remain critical challenges. Digital health tools offer promising solutions, yet their integration into MOUD programs has been limited. This study evaluates the implementation of Recovery Connect, a mobile application designed to enhance engagement, communication, and adherence in MOUD treatment.MethodsThis observational study assessed the adoption and impact of Recovery Connect across 53 opioid treatment clinics over 12 months. A total of 11,495 patients and 302 mental health professionals (MHPs) engaged with the app, which facilitated real-time patient-clinician communication, self-monitoring, and access to evidence-based resources. Patient acceptance, engagement patterns, and clinical outcomes, particularly 30-day retention, were analyzed using survey responses, app usage metrics, and historical retention data.ResultsPatient and clinician acceptance of the app was high, with 83.7% of patients who completed baseline acceptance survey expressing intent to use it. Early engagement—particularly self-monitoring and clinician-initiated messaging—was significantly associated with increased retention. Compared to historical data, 30-day retention improved by 12.2% across all clinics and by 13.2% in Arizona-based clinics. Patients with higher app engagement and more frequent clinician interactions had significantly greater odds of remaining in treatment.ConclusionDigital tools such as Recovery Connect show promise in addressing key barriers to MOUD retention by enhancing patient accountability, self-monitoring, and clinician-patient communication. These findings support the integration of digital interventions into standard MOUD care, with future research needed to assess long-term retention and scalability.